An Electronic Health Record - Public Health (EHR-PH) System Prototype for Interoperability in 21(st) Century Healthcare Systems - Orlova, Anna O. (American Medical Informatics Association, 2005)
Information exchange, enabled by computable interoperability, is the key to many of the initiatives underway including the development of Regional Health Information Exchanges, Regional Health Information Organizations, and the National Health Information Network. These initiatives must include public health as a full partner in the emerging transformation of our nation’s healthcare system through the adoption and use of information technology. An electronic health record - public health (EHR-PH) system prototype was developed to demonstrate the feasibility of electronic data transfer from a health care provider, i.e. hospital or ambulatory care settings, to multiple customized public health systems which include a Newborn Metabolic Screening Registry, a Newborn Hearing Screening Registry, an Immunization Registry and a Communicable Disease Registry, using HL7 messaging standards. Our EHR-PH system prototype can be considered a distributed EHR-based RHIE/RHIO model - a principal element for a potential technical architecture for a NHIN.